A Three-Tiered Model for Requirements in Digital Twin Architectures: Data, Intelligence and Interaction - Correia, Daniel Mangabeira; Martins, Valeria Farinazzo; Silveira, Ismar Frango (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2025: Anais do XXVII Simpósio de Realidade Virtual e Aumentada, 2025)
Digital Twins (DTs) have emerged as a transformative paradigm for real-time monitoring, simulation, and optimization of physical systems across domains such as manufacturing, energy, and education. However, the effectiveness and scalability of DTs applications are closely tied to the rigorous definition of their functional and non-functional requirements. This paper investigates the foundational role of requirements engineering in the design and deployment of DTS systems, emphasizing key aspects such as data acquisition, interoperability, real-time synchronization, security, and user interaction. Drawing from existing frameworks and case studies, we propose a three-tiered architectural model that organizes requirements across data, processing, and interaction layers. The study also highlights persistent gaps in current approaches—particularly the lack of linkage to measurable quality attributes and the absence of systematic methods for eliciting and evolving requirements. By analyzing domain-specific examples from education and energy, we demonstrate the importance of contextualizing requirements to ensure fidelity, usability, and operational effectiveness. This work contributes to the ongoing formalization of Digital Twin Engineering and proposes directions for future research toward scalable, adaptive, and ethically aligned DTs ecosystems.